The Overview Of Gadget Use and Its Impact on the Spiritual Development of Youth - Benu, Jhuarnydh; Weraman, Pius; Mage, Mernon Yerlinda Carlista (Journal of Health and Behavioral Science, 2025)
This study aims to analyze the use of gadgets and their impact on the spiritual development of teenagers within the church community. The background of this research identifies that today’s youth spend more time with gadgets, both for entertainment and learning, compared to spiritual activities such as prayer and Bible reading. A qualitative method was employed, utilizing interviews and observations with teenagers in the church. The findings reveal that excessive gadget use disrupts teenagers' focus during worship, with many preferring to engage with social media apps or play games during service time. Additionally, the research highlights the significant role of parents and educators in guiding teenagers to balance their time between gadget use and spiritual activities. The conclusion emphasizes the importance of awareness regarding the negative effects of uncontrolled gadget use, as well as the need for a wise approach in leveraging technology to support the spiritual growth of teenagers.